Bone Marrow Stromal Cells Alleviate Secondary Damage in the Substantia Nigra After Focal Cerebral Infarction in Rats - Jin, Jizi; Tang, Yanyan; Li, Kongping; Zuo, Xialin; Zhan, Lixuan; Sun, Weiwen; Xu, En (Frontiers in Cellular Neuroscience, 2019)
Transplantation of bone marrow stromal cells (BMSCs) is a promising therapy for ischemic stroke. Previously, we had reported that the secondary degeneration occurred in the ipsilateral substantia nigra (SN) after permanent distal branch of middle cerebral artery occlusion (dMCAO) in Sprague-Dawley rats. However, whether BMSCs have neurorestorative effects on the secondary damage in the SN after focal cerebral infarction has not known. In this study, rats were subjected to dMCAO followed by intravenous administration of BMSCs 1 day later. We found that transplanted BMSCs survived and migrated to cortical infarct areas and ipsilateral SN. Furthermore, BMSCs promoted neurogenesis through proliferation and differentiation in the SN after dMCAO. Rats implanted with BMSCs showed significant improvement in their performance of modified neurological severity scores and adhesive-removal test. Engrafted BMSCs enhanced survival of dopaminergic neuron, reduced gliosis in the ipsilateral SN, and increased contents of dopamine (DA) and its metabolites in the ipsilateral striatum after dMCAO. With pseudorabies virus-152 as a retrograde tracer, we also demonstrated that BMSCs could effectively enhance the cortico-striatum-nigral connections. These results suggest that BMSCs transplantation exerts neurorestorative effects after cortical infarction through promoting endogenous neurogenesis, increasing contents of DA and its metabolites, alleviating the secondary neuronal damage in the SN, enhancing the cortico-striatum-nigral projections pathway, and finally improving the neurological functional outcome.